Marketing Politics of Government to Encourage Participation in Television Digitisation Programs - Desayu, Surya Eka; Mamat, Hkikmat Mahi (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to photograph the political policies of the Government of Indonesia in peddling the Migration Program of Analog Television Broadcasts to Digital Television Broadcasts, so that a political marketing model is found. This program faces tough challenges, among others, the uneven understanding of society due to the wide area and the large number of television viewers. The government as a political superstructure actor must comprehensively communicate politics to encourage public participation in television digitalization through a form of political marketing. Through interpretive subjective approaches, qualitative methods, and descriptive juridical normative research types of laws and regulations that contain analog-to-digital migration substances as well as data collection techniques for normative studies, observations, and focus group discussions, this research finds a model of government political marketing in television digitization is carried out in stages using government structures, starting from the central government, provincial governments, to district/city governments. The television digitization model can be called the multiple levels of government model. Through this model, it is optimistic that the public's understanding of the digitization of television programs will be evenly distributed.